Village Apparatus Training Regarding Good Village Fund Management in Indonesia - Simbolon, Rosdiana; Tabita, Marcelitha; Aktama, Gede Erik; Manoppo, Franky Gerald Cliford; Simbolon, Merson (Journal Of Human And Education (JAHE), 2025)
Abstract This community service was carried out in Taduaog village, Buleleng district, North Sulawesi province, within a period of two weeks with the stages of problem formulation and solution. the author believes that training on how to use village funds for two weeks in Taduaog Village, North Sulawesi is believed to be a solution to the problem of using village funds that are less productive and still use old methods. It is hoped that with this training, the skills of the Taduaog Village apparatus, North Sulawesi can increase and become a solution to existing problems. Keywords: Vliiage Apparatus, Training, Village Fund